Predicting the Happiness of Adolescents Based on Coping Styles and Religious Attitudes - Fariddanesh, Marjan (Journal of religion and health, 2019)
The study aimed to predict the happiness of adolescents based on coping styles and religious attitudes. To this end, the correlational research methodology was used. In total, 381 subjects were selected from adolescents of Semnan (Eastern province of Iran), using multistage clustering sampling method. Research tools were Ways of Coping Questionnaire by Lazarus, Golriz and Barahani's Religious Attitude Questionnaire, and Oxford Happiness Questionnaire. Data analysis was performed in SPSS using Pearson's correlation coefficient and multiple regression analysis. Results of Pearson's correlation demonstrated a significant positive relationship between happiness of adolescents and variables of problem-focused coping styles (r = 0.31, P < 0.01) and religious attitudes (r = 0.129, P < 0.05). Meanwhile, a negative significant association was observed between emotion-focused coping styles and happiness (r = ?0.184, P < 0.01). Moreover, results of multiple regression analysis indicated that the listed variables explained 17% of the variance of happiness in totality. According to the results, it is recommended that use of problem-focused styles be emphasized in addition to strengthening of religious attitudes to increase the happiness of adolescents.